2013
DOI: 10.1155/2013/680816
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nuclear Nox4 Activity by Plumbagin: Effect on Proliferative Capacity in Human Amniotic Stem Cells

Abstract: Human amniotic fluid stem cells (AFSC) with multilineage differentiation potential are novel source for cell therapy. However, in vitro expansion leads to senescence affecting differentiation and proliferative capacities. Reactive oxygen species (ROS) have been involved in the regulation of stem cell pluripotency, proliferation, and differentiation. Redox-regulated signal transduction is coordinated by spatially controlled production of ROS within subcellular compartments. NAD(P)H oxidase family, in particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…3A), that is a critical point to be investigated one by one, in order to find a correlation between the hAFSCs profile and the physio-pathological feature of the donor. We purpose that an intrinsic ROS homeostasis, depending on specific ROS sources, is an important modulator in stem cell power, independently on the age and the oxygen tension present during cultivation in vitro [3,27].…”
Section: Discussionmentioning
confidence: 99%
“…3A), that is a critical point to be investigated one by one, in order to find a correlation between the hAFSCs profile and the physio-pathological feature of the donor. We purpose that an intrinsic ROS homeostasis, depending on specific ROS sources, is an important modulator in stem cell power, independently on the age and the oxygen tension present during cultivation in vitro [3,27].…”
Section: Discussionmentioning
confidence: 99%
“…One of the primary cellular mechanisms of ROS production involves the oxidation of nicotinamide adenine dinucleotide phosphate (NADPH) by NADPH oxidase (Nox) . Of the several Nox homologs expressed in stem cells, Nox2 and Nox4 are the most abundant ( ) , and the ROS produced by Nox2/Nox4 have been linked to many aspects of stem cell biology, including the proliferation of neural stem cells , stemness and proliferation in amniotic‐fluid stem cells , the mobilization of bone‐marrow progenitor cells in response to ischemic injury, chondrogenic , and neural‐stem cell differentiation , and the differentiation of cardiac precursor cells into smooth‐muscle cells and cardiomyocytes . Nox‐mediated ROS production also regulates migration and gene expression in stem cells , but the role of Nox2 and Nox4 in stem cell self‐renewal has yet to be thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of ROS is common in senescent cells. ROS have been related to the regulation of stem cell pluripotency, proliferation, and differentiation, besides being a critical factor which regulates the quiescent state of MSC [42]- [45]. The results obtained in this study showed that MDA levels obtained during the growth of stem cells from dental follicle of third molars had a significant increase between the 6th and 12th day of culture, accompanied by a high rate of cell growth.…”
Section: Discussionmentioning
confidence: 65%